Immune checkpoint molecules B7‐1 and B7‐H1 as predictive markers of pre‐eclampsia: A case–control study in a Ghana - Martin Awe Akilla; Ignatius Abowini Awinibuno Nchor; Moses Banyeh; Nafiu Amidu (Immunity, Inflammation and Disease)
Abstract Background/Aim Immune tolerance in the fetal–maternal junction is maintained by a balance in the Th1/Th2 system. Th1‐type immunity is associated with pro‐inflammatory cytokines and immune checkpoint molecules (ICMs) such as B7‐H1, while Th2‐type immunity is characterized by anti‐inflammatory cytokines and ICMs such as B7‐1. Any imbalance in the Th1/Th2 immune system may lead to adverse pregnancy outcomes such as pre‐eclampsia (PE). Hitherto, the potential of serum B7‐1 and B7‐H1 proteins as early markers of PE has not been explored in the Ghanaian population. Materials and Methods This was a case–control study from May 2020 to April 2022 at the War Memorial and the Upper East Regional Hospitals. The study involved 291 women, including 180 (61.9%) with normotensive pregnancy and 111 (38.1%) with PE. Venous blood samples were collected and assayed for blood cell count, serum interleukins (ILs)‐4, ‐6, ‐12, ‐18, and TNF‐α as well as serum B7‐1 and B7‐H1 proteins. Results The monocyte count (p = .007), the serum levels of IL‐18 (p = .035), TNF‐α (p = .001), and B7‐H1 (p = .006) were significantly higher in PE than in normotensive pregnancy. In addition, the monocyte count (p = .002), the serum levels of IL‐12 (p = .029), TNF‐α (p = .016), and B7‐1 (p = .009) levels were significantly higher in the third trimester than the second trimester PE. In predicting PE, the area under the curve of cytokines and ICMs ranged from 0.51 for IL‐6 to 0.62 for TNF‐α. Conclusion PE may be characterized by a dominant Th1‐type immunity with higher levels of pro‐inflammatory cytokines and B7‐H1 proteins, but these variables may not be suitable for predicting PE.